Key Elements for the Design of a Wine Route. The Case of La Axarquía in Málaga (Spain) - Cruz-Ruiz, Elena de los Reyes; Zamarreño-Aramendia, Gorka; Ruiz-Romero-de-la-Cruz, Elena María (MDPI, 2020)
The design of enotourist routes represents an opportunity for the sustainable development of rural territories. This qualitative study was structured in three parts to reach a cohesion model representing the academic literature, visitors, and winemakers. This research focused on the region of La Axarquía in Málaga (Spain) because of its wine and tourist tradition. In relation to the methodology, this study used content analysis techniques for the analysis of both the relevant literature and the questionnaires completed by all the winemakers of the territory, 60 tourists who visited the wineries, and the 10 most representative agents linked to the tourist development of this region. The findings provided a model with the elements to be taken into account in the creation of a wine route or itinerary in any destination of the world. The application of this model will contribute to the creation of new tourist policies that can move towards e cient progress of the region.
Keywords: Vino; Desarrollo rural; Enología; Sustainability and development; Wine routes and tourism; Business model design; Wineries; Heritage and culture; Rural tourism; Málaga (Axarquía)